Modern agriculture aid - K. G. Kalaiselvi, V; Keerthana, B (International Journal of Engineering and Technology, 2018)
Farming is the primary occupation in India. People depend on it to survive but no support is provided for them when they struggle to sup-port our living. One main issue in this industry is to manage the work done every day and to manage the post production products. There might be a scenario where the worker would have been abnormal which might lead them to leave the work incomplete. There needed a way for the farmer to easily find about the work done in his farm and about the workers. The proposed solution has two devices and an android application which focuses on monitoring the workers, knowing the work duration and recording the quantity of the product obtained as outcome of the process. It will make sure that the worker gets paid only if they work and will let the farmer to look after things from his/her home. The solution includes a way to authenticate the worker and record their time of entry, to verify the health condition of the worker, to track the duration of work done (Supports Salary Payment), to give basic crop characteristics for (novice) farmers, to allow the farmer to store expenditure details, to add-on the quantity of the outcome of the production into the database. It will be helpful for a novice in under-standing the farming process and will also assure a profit by aiding the farmers in understanding the requirements and expenditure and in calculation of payment for a worker based on their work.Â Â